Photodeposition as a facile route to tunable Pt photocatalysts for hydrogen production: on the role of methanol. Issue 1 (18th November 2015) - Jiang, Zhi; Zhang, ZheYu; Shangguan, Wenfeng; Isaacs, Mark A.; Durndell, Lee J.; Parlett, Christopher M. A.; Lee, Adam F.
Abstract : Pt photodeposition over titania in the presence of high methanol concentrations promotes the genesis of highly dispersed, metallic nanoparticles, active for photocatalytic hydrogen production. Abstract : Photodeposition of H2 PtCl6 in the presence of methanol promotes the formation of highly dispersed, metallic Pt nanoparticles over titania, likely via capture of photogenerated holes by the alcohol to produce an excess of surface electrons for substrate-mediated transfer to Pt complexes, resulting in a high density of surface nucleation sites for Pt reduction. Photocatalytic hydrogen production from water is proportional to the surface density of Pt metal co-catalyst, and hence photodeposition in the presence of high methanol concentrations affords a facile route to optimising photocatalyst design and highlights the importance of tuning co-catalyst properties in photocatalysis.